Competencies for Advancing Transformations Towards Sustainability - Redman, Aaron; Wiek, Arnim (Frontiers in Education, 2021)
Advancing transformations towards sustainability calls for change agents equipped with a new set of competencies. Such sustainability competencies have been articulated with multiplicity and ambiguity, which is counterproductive to joint and accelerated progress. A unified framework of sustainability learning objectives would provide guidance to students, educators, and administrators of sustainability programs. To this end, we carried out a systematic review of the relevant literature. After scanning thousands of publications, we identified over 270 peer-reviewed articles of highest relevance, spanning two decades. Despite appearance otherwise, we found that there is a high level of agreement among scholars over the sustainability competencies that students should be trained in. Expanding on the five key competencies, namely, systems-thinking, anticipatory, normative, strategic, and interpersonal competence, that have gained widespread use, this article synthesizes the new suggestions made over the past decade into a unified framework. It centers on 8 key competencies in sustainability (the 5 established and 3 emerging—intrapersonal, implementation, and integration competence), which are complemented by separate disciplinary, general, and other professional competencies. This comprehensive framework of key competencies in sustainability is applicable across disciplines and can guide faculty, students, and practitioners in their joint efforts to advance transformations towards sustainability.